Dekonstruksi Nilai Moral Kepemimpinan dan Kesetiaan Rama dalam Novel Sinta Obong Karya Ardian Kresna: Teori Jacques Derrid - Azzahra, Ayshaputri Raihana; Wibowo, Sekar Hayyu; Ainurohma, Intan; Rizqina, Naela Zahwa; Faza, Atika Nur Dhi’fana; Warsiman, Warsiman; Rizal, Maulfi Syaiful (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The nature and attitude of a wise leader is sometimes not in line with its implementation. Knights with leadership morals and loyalty that should be a good reflection of the people can be the opposite. The focus of this research is the analysis of the novel Sinta Obong by Ardian Kresna by utilizing Jacques Derrida's deconstruction theory. In contrast to ordinary reading that seeks the true meaning of the text, deconstructive reading focuses on discovering the ignorance or failure of the text in closing itself with a single meaning or truth. The method used is descriptive qualitative. Data collection techniques with library techniques, reading, and note taking. The results showed data in the form of Rama Wijaya's traits that contradict the soul of a wise leader and a loyal partner, (1) narcissism, (2) selfish and stubborn, (3) closing the right to speak, (4) naive and unstable, (5) tarnishing loyalty, and (6) arrogant and cruel. From these traits, it can be seen that Rama Wijaya is still far from the noble nature of a knight.